Pengaruh Ketinggian Dan Redaman Dalam Meningkatkan Daya Keluaran Pada Panel Surya - Aminullah, Moh. Wahyu; Iskandar, Iskandar; Basir, Yuslan (PROtek : Jurnal Ilmiah Teknik Elektro, 2022)
One of the problems of laying solar panels and attenuation will affect the output power of the solar panels. Several other studies have been carried out with different heights and the addition of attenuation will increase the output power of solar panels. This research was conducted using experimental methods for 6 designs that have been planned. Design 1 solar panel without height and without attenuation, design 2 solar panels without height using attenuation, design 3 solar panels with a height of 10 m and without attenuation, design 4 solar panels with a height of 10 m and use attenuation, design 5 solar panels with a height of 75 m without using attenuation and design 6 solar panels with a height of 75 m and using attenuation. This study aims to determine the effect of changing the height of the solar panels and adding attenuation to see how much power the solar panels produce when they are sunny. Measurement of voltage (Voc) and current (Isc) was carried out for 5 days. The results showed that the highest average output power of solar panels was in design 6 of 45.16 W, while the lowest average output power of solar panels was in design 1 of 41.43 W. The output power of solar panels in design 6 is 8 .3% more than design 1